2017
DOI: 10.1021/acs.jpcb.6b11207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structure and Orientation of Melittin Bound to Acidic Lipid Bilayers, As Revealed by Solid-State NMR and Molecular Dynamics Simulation

Abstract: Melittin is a venom peptide that disrupts lipid bilayers at temperatures below the liquid-crystalline to gel phase transition temperature (T). Notably, the ability of melittin to disrupt acidic dimyristoylphosphatidylglycerol (DMPG) bilayers was weaker than its ability to disrupt neutral dimyristoylphosphatidylcholine bilayers. The structure and orientation of melittin bound to DMPG bilayers were revealed by analyzing the C chemical shift anisotropy of [1-C]-labeled melittin obtained from solid-state C NMR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…In this case, an axially symmetric powder pattern is observed as shown in lecithin-melittin bilayer systems (Fig. 1(b) and (g)) [15,20,21]. …”
Section: Solid-state Nmr Spectroscopy For Elucidating the Structures mentioning
confidence: 58%
See 4 more Smart Citations
“…In this case, an axially symmetric powder pattern is observed as shown in lecithin-melittin bilayer systems (Fig. 1(b) and (g)) [15,20,21]. …”
Section: Solid-state Nmr Spectroscopy For Elucidating the Structures mentioning
confidence: 58%
“…Solid-state NMR is particularly well suited for elucidating the dynamics, topologies, orientations, and high resolution structures of peptides in the lipid bilayer environment using membrane mimetics such as lipid vesicles, bicelles or lipid nanodiscs/macrodiscs. While several studies have reported valuable structural and functional insights into a variety of AMPs (including magainins, MSI-78, LL-37, pardaxin, protegrin and other designed peptides), the use of chemical shift oscillation analysis in elucidating the detailed structure and orientation of the membrane bound state of antibacterial peptides such as melittin [15,20,21], bonbolitin II [49], lactoferrampin [45] and alamethicin [50] reported in the literature are highlighted below.…”
Section: Dynamic Structure Of Antimicrobial Peptides In Membrane Envimentioning
confidence: 99%
See 3 more Smart Citations